1997
DOI: 10.1103/physrevlett.79.4218
|View full text |Cite
|
Sign up to set email alerts
|

Wigner Solid on the Free Surface of SuperfluidH3e

Abstract: We report the measurement of electrical transport of the two-dimensional Wigner solid (WS) formed on the free surface of superfluid 3 He-B down to 230 mK. The resistance R͑T ͒ dramatically decreases as temperature T decreases, obeying Arrhenius' law, R͑T͒~exp͓2D͑T͒͞k B T͔, with D͑T ͒ which we assign to the superfluid energy gap. That is, the scattering of 3 He quasiparticles by the WS determines the transport. The resistance depends systematically on the static electric field which presses the WS toward the li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 19 publications
0
22
0
Order By: Relevance
“…The existence of the quantized capillary surface waves, or ripplons, earlier proposed by Atkins [7] in order to explain surface tension data, has been clearly proven in experiments with a two-dimensional plasma resonance in surface electrons [9]. Later, ripplons [10] as well as scattering of surface electrons with Fermi quasi-particles from bulk liquid [11] were detected on liquid 3 He. Soon after that, it was found that the mobility of surface electrons on 3 He deviates drastically from the single-electron-ripplon scattering theory below 70 mK [12].…”
mentioning
confidence: 80%
“…The existence of the quantized capillary surface waves, or ripplons, earlier proposed by Atkins [7] in order to explain surface tension data, has been clearly proven in experiments with a two-dimensional plasma resonance in surface electrons [9]. Later, ripplons [10] as well as scattering of surface electrons with Fermi quasi-particles from bulk liquid [11] were detected on liquid 3 He. Soon after that, it was found that the mobility of surface electrons on 3 He deviates drastically from the single-electron-ripplon scattering theory below 70 mK [12].…”
mentioning
confidence: 80%
“…We had previously found that at sufficiently weak driving, the WS transport on liquid 3 He is Ohmic [3,5]. In the Ohmic regime, the WS mobility m has an interesting temperature dependence, and it is well explained by a linear theory [4].…”
Section: Experimental Methods and Resultsmentioning
confidence: 97%
“…We have measured the low-frequency ac resistance R of the SSE by a capacitive coupling method [3,9]: A Corbino disk (30 and 20 mm in outer and inner diameters, respectively, and 0.1 mm gap width) is located 1.0 min beneath the helium surface. The SSE were formed by thermoionic emission of a tungsten filament, and were kept by a static holding electric field E t between the Corbino electrode and a disk electrode which is located 2.5 mm above the liquid surface.…”
Section: Experimental Methods and Resultsmentioning
confidence: 99%
See 2 more Smart Citations